Carex procumbens (Carex sect. Rhomboidales, Cyperaceae), a new species from Hainan, China - Yang, Hu-Biao; Li, Xiao-Xia; Bai, Chang-Jun; Wang, Wen-Qiang; Yu, Dao-Geng; Dong, Rong-Shu; Liu, Guo-Dao (Phytotaxa, 2015)
Carex procumbens, a new species of Carex sect. Rhomboidales from Hainan, China, is described and illustrated. The new species is similar to C. longipetiolata but differs in culms soft and usually prostrate on the ground, having narrower leaves with the leaf base gradually narrowed, with 2–3 spikes, terminal spike 8–12 mm long, lateral spikes 5–15 mm long and loosely flowered, staminate glumes ovate with green middle vein and apex rounded, pistillate glumes ovate-lanceolate ca. 6 mm and middle vein excurrent into a short awn for ca. 2 mm, perigynia fusiform and glabrous, nutlet brown to dark brown and ovate-rhomboid, nutlet ca. 7 mm long and with a short curved beak.